Local approach to fracture based prediction of reactor pressure vessel lifetime - Kotrechko, S.A.; Meshkov, Yu.Ya. (Проблемы прочности, 2009)
New version of the local approach to fracture is presented. Within the framework of this approach a new methodology is developed, which supposes prediction of radiation life time of a reactor pressure vessel not by ultimate shift of the Charpy critical temperature, ΔTк, or by reference temperature, ΔT0 but by the condition of brittle fracture initiation of irradiated metal ahead of a crack tip in reactor pressure vessels.